2013
DOI: 10.1111/1758-2229.12088
|View full text |Cite
|
Sign up to set email alerts
|

Environmental distribution of two widespread uncultured freshwater Euryarchaeota clades unveiled by specific primers and quantitative PCR

Abstract: Quantitative environmental distribution of two widely distributed uncultured freshwater Euryarchaeota with unknown functional role was explored by newly designed quantitative PCR primers targeting the 16S rRNA gene of clades Miscellaneous Euryarchaeota Group (MEG, containing the groups pMC2A384 and VALII/Eury4) and Deep-Sea Euryarchaeotal Groups (DSEG, targeting the cluster named VALIII containing the DHVE-3/DSEG, BC07-2A-27/DSEG-3 and DSEG-2 groups), respectively. The summer surface plankton of 28 lakes was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Woesearchaeota”) archaeon most similar to archaeon GW2011_AR9 (85); (x) “ Ca. Micrarchaeota” (Eury4AB group) archaea most similar to clone C1AA1CA10 locus tag GU127467 (86, 87); (xi) “ Ca. Altiarchaeales” archaea (88–91); (xii) Crystal Geyser groundwater archaea (91), one of which is similar to clone SCA130 locus tag EU735580 (92); (xiii) locus tag Z7ME43 or Theionarchaea archaea (93); (xiv) Arc 1 group or “ Ca.…”
Section: Resultsmentioning
confidence: 99%
“…Woesearchaeota”) archaeon most similar to archaeon GW2011_AR9 (85); (x) “ Ca. Micrarchaeota” (Eury4AB group) archaea most similar to clone C1AA1CA10 locus tag GU127467 (86, 87); (xi) “ Ca. Altiarchaeales” archaea (88–91); (xii) Crystal Geyser groundwater archaea (91), one of which is similar to clone SCA130 locus tag EU735580 (92); (xiii) locus tag Z7ME43 or Theionarchaea archaea (93); (xiv) Arc 1 group or “ Ca.…”
Section: Resultsmentioning
confidence: 99%
“…AOA have been shown to experience photoinhibition (Merbt et al ., ), and this is in agreement with the scarce presence of AOA detected in the surface waters analysed here. Previous studies in the Pyrenean area explored the different archaeal populations detected around the thermocline and in deeper waters, mostly AOA (Auguet et al ., ; Auguet and Casamayor, ; Restrepo‐Ortiz et al ., ), and the spatio‐temporal distribution of euryarchaeotal MEG (Micrarchaeota and Diapherotrites) and DSEG (Aenigmarchaeota) clusters (Restrepo‐Ortiz and Casamayor, ), but missed the recently coined lineages Pacearchaeota and Woesearchaeota (Castelle et al ., ). A positive and strongly significant relationship between the 16S rRNA gene abundance (qPCR) of DSEG and putative AOA suggested that Aenigmarchaeota and AOA may share a closely related ecological niche, mainly in bottom waters of a deep alpine lake where reduced inorganic nitrogen compounds exist (Restrepo‐Ortiz and Casamayor, ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in the Pyrenean area explored the different archaeal populations detected around the thermocline and in deeper waters, mostly AOA (Auguet et al ., ; Auguet and Casamayor, ; Restrepo‐Ortiz et al ., ), and the spatio‐temporal distribution of euryarchaeotal MEG (Micrarchaeota and Diapherotrites) and DSEG (Aenigmarchaeota) clusters (Restrepo‐Ortiz and Casamayor, ), but missed the recently coined lineages Pacearchaeota and Woesearchaeota (Castelle et al ., ). A positive and strongly significant relationship between the 16S rRNA gene abundance (qPCR) of DSEG and putative AOA suggested that Aenigmarchaeota and AOA may share a closely related ecological niche, mainly in bottom waters of a deep alpine lake where reduced inorganic nitrogen compounds exist (Restrepo‐Ortiz and Casamayor, ). Interestingly, Rubisco genes for carbon fixation have been recently found in a genome of Aenigmarchaeota (Castelle et al ., ), and this finding may potentially help to establish biogeochemical connections between the autotrophic carbon cycling and the oxidation of nitrogen compounds through Aenigmarchaeota.…”
Section: Discussionmentioning
confidence: 99%
“…Minor groups are related to the SM1K20 cluster, Aenigmarchaeota (Euryarchaeota DSEG cluster), MCG (Miscellaneous Crenarchaeotic Group, currently Bathyarcheota) and soil AOA. In subsurface and bottom waters of deeper lakes, accumulations of AOA and Aenigmarchaeota are however detected Restrepo-Ortiz and Casamayor 2013). This extensive study in the Pyrenean lacustrine district unveiled the environmental preferences and habitat breadth for the different lineages.…”
Section: Archaeamentioning
confidence: 72%